2011
DOI: 10.1155/2011/679806
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Alpha-Particle Radiation and X-Irradiation on Genes Associated with Apoptosis

Abstract: This study examined differential effects of alpha-(α-) particle radiation and X-rays on apoptosis and associated changes in gene expression. Human monocytic cells were exposed to α-particle radiation and X-rays from 0 to 1.5 Gy. Four days postexposure, cell death was measured by flow cytometry and 84 genes related to apoptosis were analyzed using real-time PCR. On average, 33% of the cells were apoptotic at 1.5 Gy of α-particle radiation. Transcript profiling showed statistical expression of 15 genes at all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…A recent study from this laboratory demonstrated that the reduction of cell proliferation elicited by the α-emitting radioimmunotherapeutic, 212 Pb-TCMC-trastuzumab, is associated with G2/M arrest, blockage of double-strand DNA damage repair and increased apoptosis 5 . To date, gene modulations associated with α-particle radioimmunotherapy (RIT) have not been defined 9 , 10 . Therefore, to better understand the molecular basis of α-particle RIT, the changes in gene expression in response to α-emitter RIT were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from this laboratory demonstrated that the reduction of cell proliferation elicited by the α-emitting radioimmunotherapeutic, 212 Pb-TCMC-trastuzumab, is associated with G2/M arrest, blockage of double-strand DNA damage repair and increased apoptosis 5 . To date, gene modulations associated with α-particle radioimmunotherapy (RIT) have not been defined 9 , 10 . Therefore, to better understand the molecular basis of α-particle RIT, the changes in gene expression in response to α-emitter RIT were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chauhan et al [176] detected the expression of Fas and TNF-a in human monocytic THP-1 cells after the cells were irradiated with alpha particles and X-rays with mean absorbed doses from 0 to 1.5 Gy; however, the expression levels of TNF-a were significantly higher for a-particle irradiation. TNF-a could activate the NF-jB/COX-2 signal pathway to induce inflammation-type effect in bystander cells, whereas cyclooxygense-2 (COX-2) was identified as a ''central component'' of RIBE [74] To cite another example, Anzenberg et al [177] found LET-dependent differences in the signal that was released from DU-145 human prostate carcinoma cells by irradiating these cells with alpha particles or 250 kVp X-rays.…”
Section: Studies On High-let-radiation Induced Non-targeted Effectsmentioning
confidence: 99%
“…Despite a long history of studies regarding the mechanisms of action of paclitaxel and photon radiation used individually, little is understood about how paclitaxel and radiation together promote in vivo tumor cell death. In particular, gene modulations associated with the cytocidal response have not been clearly defined following exposure of cells to α-particle RIT combined with paclitaxel [13] , [14] . A recent report from this laboratory showed that paclitaxel potentiates 212 Pb-trastuzumab cytotoxicity, in part, by perturbing the mitotic spindle checkpoint [15] .…”
Section: Introductionmentioning
confidence: 99%